The complete idiot's guide to Microsoft Word 97 - Bobola, Daniel T. 4 0 16; 5 (Indianapolis, IN : Que, 1996)
Guide to using the word processing program Microsoft Word 97, with information on installing and formatting options, basic editing and text formating, proofing tools, saving, printing, adding multimedia features, creating tables and graphics, using templates, and getting around the Internet.
Includes index.
Library Journal
Adult;Adult
Keywords: 2 -- 0; 6; Microsoft Word.;Microsoft Word; Word processing.;Word processing; 20; 2